Menyoal Branding Kabupaten Bandung sebagai Daerah Religius dan Sejahtera melalui Program Incentive Guru Ngaji Tahun 2021-2022 - Adiwilaga, Rendy; Mustofa, Mustabsyirotul Ummah; Ikhsan, Teja Nur (Universitas Medan Area, 2024)
Along with the election of Dadang Supriatna-Sahrul Gunawan as the elected Regent and Vice Regent of Bandung, both prioritized Bandung Regency as a religious and prosperous area as stated in their vision. One of the manifestations of this vision is the Incentive program. Ngaji teachers in the Bandung Regency area. The Ngaji Teacher Incentive Program is in principle one of the flagship programs of Regent Dadang Supriatna, during his campaign for the candidacy for Regent of Bandung Regency, where when he was elected, the implementation of the policy was then fully submitted to the Bandung Regency Regional Government through the basis of Perbup No. 51 of 2021 concerning Guidelines for Providing Ngaji Teacher Incentives and specifically, the implementor is the Education Office. The Quranic Teacher Incentive Program is targeted at religious educators in Bandung Regency with the aim of improving the welfare of Quranic teachers as religious educators by providing monthly incentives in the form of non-cash transfer funds as well as funds for BPJS Health and BPJS Employment. 17,000 Koranic teachers in Bandung Regency in the process then became the target beneficiaries of the incentive money assistance. There are 23,000 Quranic teachers in Bandung district, and the government has budgeted Rp 109 billion for Quranic teacher incentive assistance. The results of the study show that the implementing committee officers involved in implementing the Koranic Teacher Incentive Program policy have not implemented the policy optimally. The lack of optimal policy implementation is motivated by the lack of selectivity of the sub-district and village parties in implementing the policy, resulting in pros and cons and social jealousy. In addition, there are also differences regarding the nominal incentive money given according to members of the Dinas and village officials. In this Quranic teacher incentive program, it can also be concluded that economic conditions are the most important influence in the implementation of the Quranic Teacher Incentive Program. Because if there is no financial resource support, the financial resources, the Quranic Teacher Incentive Program will not be implemented.